Pengaruh Pendidikan Kewirausahaan, Dukungan Keluarga dan Self Efficacy Terhadap Minat Berwirausaha Mahasiswa: The Influence of Entrepreneurship Education, Family Support, and Self-Efficacy on Students' Entrepreneurial Interest - Mauludiani, Yunia Sri; Nurdianti, Raden Roro Suci; Hermawan, Yoni (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
The problem in this study concerns the low entrepreneurial interest among Economics Education students. This research aims to analyze the influence of entrepreneurship education, family support, and self-efficacy on the entrepreneurial interest of Economics Education students. The research method used was a survey with an explanatory research design. The study population included 146 students from the 2021–2022 cohort of the Economics Education program. The sample was selected using a purposive sampling method. Data collection for this study utilized a questionnaire, and the data analysis technique applied was multiple linear regression analysis. The research findings indicate that there is a positive and significant influence of entrepreneurship education on entrepreneurial interest, with a significance value of 0.000. There is a positive and significant influence of family support on entrepreneurial interest, with a significance value of 0.037. There is a positive and significant influence of self-efficacy on entrepreneurial interest, with a significance value of 0.013. Furthermore, there is a positive and significant influence of entrepreneurship education, family support, and self-efficacy simultaneously on entrepreneurial interest, with a significance value of 0.000.